2001
DOI: 10.1038/35086540
|View full text |Cite
|
Sign up to set email alerts
|

Diamagnetic activity above Tc as a precursor to superconductivity in La2-xSrxCuO4 thin films

Abstract: Superconductors show zero resistance to electric current, and expel magnetic flux (the Meissner effect) below the transition temperature (Tc). In conventional superconductors, the 'Cooper pairs' of electrons that are responsible for superconductivity form only below Tc. In the unconventional high-Tc superconductors, however, a strong electron correlation is essential for pair formation: there is evidence that some pairs are formed above Tc in samples that have less than the optimal density of charge carriers (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
90
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(106 citation statements)
references
References 25 publications
11
90
0
2
Order By: Relevance
“…We have already mentioned the recent measurements of magnetic domains above T c which has been interpreted as a diamagnetic precursor to the Meissner state, produced by performed pairs in underdoped La 2−x Sr x CuO 4 thin films 20 . The existence of superconducting clusters between T * and T c easily explains the appearance of local diamagnetic or Meissner domains and, if there is a temperature gradient in the sample, the local flux flows and produces the dynamic flux flow state 28 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have already mentioned the recent measurements of magnetic domains above T c which has been interpreted as a diamagnetic precursor to the Meissner state, produced by performed pairs in underdoped La 2−x Sr x CuO 4 thin films 20 . The existence of superconducting clusters between T * and T c easily explains the appearance of local diamagnetic or Meissner domains and, if there is a temperature gradient in the sample, the local flux flows and produces the dynamic flux flow state 28 .…”
Section: Discussionmentioning
confidence: 99%
“…It reflects the nano-scale variations of the superconducting energy gap or the nano-scale variations on the density of charges in the material. This percolating scenario can be understood by analyzing the scanning SQUID microscopy magnetic data which makes a map of the expelled magnetic flux (Meissner effect) domains on LSCO films 20 . This experiment shows the regions where the Meissner effect continuously develops from near T * to temperatures well below the percolating threshold T c .…”
Section: Introductionmentioning
confidence: 99%
“…This is another manifestation of the intrinsic tendency toward microscopically inhomogeneous states (the list of references simply too long to be reproduced here). Finally, recent scanning SQUID microscopy study by Iguchi et al [17] have reported the existence of diamagnetic activity above T c in La 2−x Sr x CuO 4 . The phenomenon is found at temperatures as high as 80 K, which is remarkable!…”
Section: Inhomogeneities In Manganites and Other Com-poundsmentioning
confidence: 99%
“…In particular, much of this discussion addresses the character of the local order in a quantum disordered phase close to a quantum critical 1 For brief reviews of the current evidence on various types of stripe order in the cuprates, see (Carlson et al, 2003;Castro Neto and Morais Smith, 2003;Emery et al, 1999;Orenstein and Millis, 2000;Sachdev, 2002;Zaanen, 2000) 2 Fluctuations associated with off-diagonal (i.e., superconducting) order are best studied using different strategies; see, for example, Iguchi et al, 2001;Jankó et al, 1999;Ussishkin et al, 2002;Wang et al, 2001;Xu et al, 2000) 3 For reviews of neutron and X-ray evidence of stripes, see (Emery et al, 1999;Tranquada, 1998a,b).…”
Section: Introductionmentioning
confidence: 99%